Religiosity and PAI Learning Motivation in Adult Islamic Education: A Quantitative Correlational Study at Tamhiedul Muballighat, PD Persistri Bandung Regency - Muthi Annisa Septyanti; Ela Komala (Institut Agama Islam Persis Bandung, 2025)
Islamic Religious Education (PAI) scholarship has almost exclusively examined the relationship between religiosity and learning motivation in formal school settings with adolescent learners. This study addresses a critical gap by investigating the same relationship in a non-formal adult Islamic education setting the Tamhiedul Muballighat programme of Pimpinan Daerah (PD) Persistri Kabupaten Bandung, West Java, Indonesia in which all participants are women aged 40 years and above. A quantitative correlational design was employed with total population sampling (n = 39), encompassing all Marhalah II participants enrolled in the 2023–2024 academic cohort. Variable X (religiosity) was operationalised across five Glock and Stark dimensions: religious belief (4.40), worship practice (4.15), religious experience (4.11), religious knowledge (3.84), and religious consequence (4.42), yielding an overall mean of 4.18 (High qualification). Variable Y (PAI learning motivation) was operationalised across five Hamzah B. Uno dimensions: desire and will to succeed (3.42), drive and learning need (3.72), future aspiration (3.73), engaging learning activities (3.57), and conducive learning environment (3.22), yielding an overall mean of 3.53 (High qualification, at the lower boundary of the High interval). Pearson Product Moment correlation analysis yielded r = 0.632 (High positive correlation), a coefficient of determination of 39.9% (KP = r² × 100), and t-hitung = 4.958 substantially exceeding t-tabel = 1.687 at α = 5%, dk = 37. The regression equation Y = 7.45 + 0.75X confirms a positive directional relationship. The 60.1% of unexplained variance reflects the distinctive challenges of adult learning: declining cognitive capacity, limited educational backgrounds, physiological constraints, and restricted study time. The findings provide the first quantitative evidence on the religiosity–learning motivation relationship for adult Muslim women in a non-formal education context, with implications for andragogical curriculum design, adult Islamic education policy, and motivational support strategies for late-life learners